Selection of preferred routing protocols of wireless sensor and actuator network nodes - Безрук, Валерий Михайлович; Зеленин, Анатолий Николаевич; Власова, Виктория Александровна; Скорик, Юлия Валериевна; Колтун, Юрий Николаевич (Eastern-European Journal of Enterprise Technologies, 2016)
The problems of routing to search for energy efficiency-optimal routes are important in wireless sensor and actuator networks. This determines the relevance of selecting a preferred option among many different routing protocols for a specific implementation. The paper considers the practical features of applying the analytic hierarchy process to select the preferred routing protocol for wireless sensor and actuator networks. A comparative analysis of the characteristics of existing routing protocols in sensor networks is performed. Experts provided paired comparisons of characteristics of 11 routing protocols. The paired comparison matrices, which allowed computing the eigenvector and priority vector components are formed. According to the maximum values of the priority vector components, the preferred routing protocol - GEAR (Geographical and Energy-Aware Routing) is selected for use in field sensor and actuator networks with localization of elements. The results confirm the applicability of the analytic hierarchy process to select the preferred routing protocol in the design of sensor and actuator networks taking into account the specified implementation requirements.